Investigation and Optimization of Grounding Grid Based on Lightning Response by Using ATP-EMTP and Genetic Algorithm - Saeid Gholami Farkoush; Tahir Khurshaid; Abdul Wadood; Chang-Hwan Kim; Kumail Hassan Kharal; Kyu-Ho Kim; Namhun Cho; Sang-Bong Rhee (Complexity)
A large number of electromagnetic transient studies have been analyzed for finding the overvoltage behavior of power system. A grounding grid of power system is so important for reducing the effect of overvoltage phenomena during a short-circuit event. Two sections are important in grounding system behavior: soil ionization and inductive behavior; this paper focuses on the inductive manner of grounding grid. The grounding grid is considered as a conductor segment; each conductor segment acts as a grounding unit. In this paper, the transient methodology is introduced to investigate the lightning effect on grounding body at each point of grounding grid in normal and optimized conditions. Genetic algorithm is applied for regular and irregular grounding grid to obtain best values of mesh size with the lower ground potential rise (GPR) as compared with the normal condition for more safety. The grounding grid is a combination of inductance, resistance, and capacitance. This model is suitable for practical applications related to fault diagnosis. Several voltages on different positions of grounding grid are described in this paper using ATP-EMTP and genetic algorithm. The computer simulation shows that the proposed scheme is highly feasible and technically attractive.